Pengaruh Pupuk Kalium Terhadap Pertumbuhan dan Produksi Beberapa Galur F7 Kacang Kedelai (Glycine max L.) - Arvita Netti Sihaloho; Irawaty Rosalyne; Dita Ramadhani (Universitas Gadjah Mada, 2025)
One of the essential macro nutrients that is highly needed in plant growth because its function cannot be replaced by other nutrients is Potassium. Soybean plants require a high amount of potassium because the growth of soybean plants is greatly influenced by potassium. This study aims to obtain the best dose of Potassium fertiliser for one F7 soybean strain selected from several strains studied so that one selected strain can be obtained. The research was conducted from October 2023 to December 2023, at the Experimental Garden of the Faculty of Agriculture, University of Simalungun with an altitude of 400-500 m above sea level. Factorial Randomised Block Design with two factors was used in this study. The first factor was 5 F7 soybean strains (G) used, namely G1 = F7.5.82.87.166.71.35.1; G2 = F7.5.82.87.166.71.35.2; G3 = F7.5.82.87.166.71.35.3; G4 = F7.5.82.87.166.75.40.1; G5 = F7.5.82.87.184.12.75.38. The second factor of KCl fertiliser (K) used was three levels, namely K1 = 75 kg/ha (18 g/plot), K2 = 150 kg/ha (36 g/plot), K3 = 225 kg/ha (54 g/plot). There were 15 treatment combinations and each combination was repeated 3 times, resulting in 45 research plots. The parameters observed were plant height (cm), number of branches (branches), number of pods per plant (pods), seed weight per plant (g), seed weight per plot (kg) and 100 seed weight (g). If the analysis of variance shows an effect, the analysis will continue using the 5% BNT test. The results showed that the strain F7.5.82.87.166.71.35.2 was the selected strain to be continued because this strain interacted best with the dose of potassium fertiliser 225 kg/ha (54 gr/plot), by producing a large and significantly different correlation value between the number of branches to the number of pods per plant, seed weight per plant and seed weight per plot (0.944**, 0.936**, 0.873**).